Lower bounds for the scheduling problem with uncertain demands - Berkoune, Djamel; Mesghouni, Khaled; Rabenasolo, Besoa (Zielona Góra: Uniwersytet Zielonogórski)
This paper proposes various lower bounds to the makespan of the flexible job shop scheduling problem (FJSP). The FJSP is known in the literature as one of the most difficult combinatorial optimisation problems (NP-hard). We will use genetic algorithms for the optimisation of this type of problems.
Keywords: flexible job shop scheduling; insertion; makespan; predicted demands; lower bounds